Demographic dividend and human capital development in the manufacturing sector in anticipation of Golden Indonesia 2045 - Nugroho, Iwan (Publisher of Widyagama University of Malang (UWG Press), 2024)
The Vision of Golden Indonesia 2045 aims to position Indonesia as a developed country with a per capita income of USD 30300, significantly reduced poverty rates, high competitiveness, and enhanced human capital. Indonesia has immense potential, particularly with its demographic dividend of 128 million workers. Therefore, human capital planning and development is required to achieve high quality performance and productivity. This article highlights the vital role of the manufacturing sector in driving economic transformation. The manufacturing industry should be prioritized for boosting human capital, by taking advantage of the demographic dividend. Suppose that the manufacturing sector will employ 25% of the workforce. In that case, by 2045, this sector will employ 51.8 million workers—an increase of 30.8 million from 20.01 million in 2024. To enhance human capital within the manufacturing sector, several strategic steps can be taken: (i) implementing education and training programs that align closely with industry needs, (ii) developing infrastructure and the overall manufacturing ecosystem, (iii) improving the quality of human resources in key manufacturing areas, particularly in palm oil, organic basic chemicals from agricultural products, machinery, and automotive spare parts, and (iv) advancing agro-industry to stimulate economic transformation and create job opportunities in the agricultural sector. JEL Classification: J10; J21; O14